Definitive Chemoradiation with Concurrent Weekly Cisplatin in the Treatment of Esophageal Squamous Cell Carcinoma – A Simplistic Approach - Ahmed, Imtiaz; Krishnamurthy, Sapna; Bhise, Rohan (Asian Pacific Journal of Cancer Care, 2021)
Purpose: Chemoradiation is the standard of care in locally advanced/ inoperable esophageal squamous cell cancer (ESCC). Though combination chemotherapy with Cisplatin and 5-Fluorouracil is the standard, it has low compliance due to toxicities and prolonged treatment time. Hence there is a window of opportunity to explore a safer chemotherapy regimen without compromising the treatment outcome. Methods: 55 patients of ESCC who were treated with definitive External Beam Radiotherapy (EBRT) to a dose of 50.4 – 59.4 Gray and concurrent weekly Cisplatin (or Carboplatin) were retrospectively evaluated for treatment efficacy and outcomes. 2 year Overall Survival (OS) and Progression Free Survival (PFS) were evaluated. Prognostic variables were assessed with respect to OS in Univariate analysis. Results: Median age at presentation was 58 years. 29 (53%) had lesion in the upper third of esophagus. 40 (72%) had T3 disease and 31 (56%) were node positive. All patients (100%) completed planned radiotherapy dose. 54 (98%) received 4 or more cycles of weekly chemotherapy. Mean overall treatment time was 43 days. Only 7 patients (12.7%) had grade 3 or more acute toxicity. 36 (65.5%) had complete response. At median follow-up of 13.7 months, the median OS was 15.2 months and 2 year OS was 42.6%. On univariate analysis, patients with comorbidities and lower third lesion had poor OS (p=0.016 and p=0.002). Stage II disease and complete response to treatment showed better OS (p=0.02 and p=0.00). Conclusion: Radical chemoradiation with weekly Cisplatin in ESCC is a simple and effective regimen which needs to be explored in larger trials.